Towards early inclusion of children in tuberculosis drugs trials: a consensus statement. Issue 6 (June 2015) - Nachman, Sharon; Ahmed, Amina; Amanullah, Farhana; Becerra, Mercedes C; Botgros, Radu; Brigden, Grania; Browning, Renee; Gardiner, Elizabeth; Hafner, Richard; Hesseling, Anneke; How, Cleotilde; Jean-Philippe, Patrick; et al.
Summary Children younger than 18 years account for a substantial proportion of patients with tuberculosis worldwide. Available treatments for paediatric drug-susceptible and drug-resistant tuberculosis, albeit generally effective, are hampered by high pill burden, long duration of treatment, coexistent toxic effects, and an overall scarcity of suitable child-friendly formulations. Several new drugs and regimens with promising activity against both drug-susceptible and drug-resistant strains have entered clinical development and are either in various phases of clinical investigation or have received marketing authorisation for adults; however, none have data on their use in children. This consensus statement, generated from an international panel of opinion leaders on childhood tuberculosis and incorporating reviews of published literature from January, 2004, to May, 2014, addressed four key questions: what drugs or regimens should be prioritised for clinical trials in children? Which populations of children are high priorities for study? When can phase 1 or 2 studies be initiated in children? What are the relevant elements of clinical trial design? The consensus panel found that children can be included in studies at the early phases of drug development and should be an integral part of the clinical development plan, rather than studied after regulatory approval in adults is obtained.